Social-Political Content Exposure on TikTok and Its Impact on University Students’ Social Behavior - Fivian Hazar Robayani; Benny Bernadus (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The rapid growth of short-video platforms has transformed how young adults engage with social and political information, potentially shaping their social behavior beyond formal political participation. This study examines the effects of exposure to social-political content and the intensity of TikTok use on students’ interpersonal competence. Using a quantitative explanatory design, data were collected from 103 undergraduate students at a private university in Bandung, Indonesia, through a structured questionnaire. Social-political content exposure, TikTok usage intensity, and interpersonal competence were measured using adapted and validated scales. Data were analyzed using multiple linear regression. The results indicate that exposure to social-political content on TikTok has a positive and statistically significant effect on students’ interpersonal competence, whereas TikTok usage intensity is negatively associated but not statistically significant. The regression model explains 31.7% of the variance in interpersonal competence, suggesting a moderate explanatory power. These findings highlight that the social impact of TikTok is driven more by the type of content consumed than by the frequency or duration of platform use. The study contributes to the literature by extending social learning and media effects perspectives to interpersonal outcomes, demonstrating that social-political content on short-video platforms can function as an informal learning resource that enhances communication and social interaction skills. In practice, the findings underscore the importance of promoting critical engagement with constructive digital content rather than focusing solely on limiting social media use. Future research is encouraged to adopt longitudinal designs and explore additional mediating factors to further understand the mechanisms linking digital content exposure and social behavior.